Technological development and concentration of stock exchanges in Europe - Heiko Schmiedel (Bank of Finland, 2001)
This paper provides an explanation of technical inefficiencies of financial exchanges in Europe as well as an empirical analysis of their existence and extent.A single-stage stochastic cost frontier approach is employed, which generates exchange inefficiency scores based on a unique unbalanced panel data set for all major European financial exchanges over the period 1985-1999.Overall cost inefficiency scores reveal that European exchanges operate at 20-25% above the efficiency benchmark.The results also affirm that size of exchange; market concentration and quality; structural reorganisations of exchange governance; diversification in trading service activities; and adoption of automated trading systems significantly influence the efficient provision of trading services in Europe.Over the sample period, European exchanges notably improved their ability to efficiently manage their production and input resources.
URN:NBN:fi:bof-20140807629
Keywords: 330; Europe; financial exchanges; panel data; technical efficiency